2019
DOI: 10.3171/2018.9.peds18470
|View full text |Cite
|
Sign up to set email alerts
|

Intraventricular tigecycline for the treatment of shunt infection: a case in pediatrics

Abstract: Ventriculoperitoneal (VP) shunt infections are seen in 3%–17% of patients with VP shunts. These infections may cause severe morbidity and mortality. Staphylococci are the most common cause of CSF shunt-associated infections, although gram-negative bacteria (especially multidrug-resistant [MDR] and extensive drug–resistant [XDR] bacteria) also play an important role. Due to increased antibiotic resistance, sometimes off-label usage of antibiotics is considered. Tigecycline is one of these antibiotics. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
(16 reference statements)
0
7
0
1
Order By: Relevance
“…Tigecycline, the glycylcycline antibiotics, has bacteriostatic effect on multidrug-resistant bacteria such as carbapenem-resistant Acinetobacter and Klebsiella pneumoniae, and its binding ability to bacterial ribosomes is stronger than that of other tetracycline antibiotics, so it is often used clinically in the treatment of complex skin and soft tissue infections, intra-abdominal infections, acquired pneumonia, and other diseases in adults [ 10 ]. Many studies showed that tigecycline had positive in vitro antibacterial activity against resistant Acinetobacter baumannii, but sole use of it may lead to resistant bacteria [ 11 , 12 ]. Cefoperazone sulbactam sodium, the broad-spectrum antibiotic, has a certain therapeutic effect on respiratory tract infections, urogenital infections, intra-abdominal infections, bone and joint infections, intracranial infections, and skin and soft tissue infections caused by sensitive bacteria [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tigecycline, the glycylcycline antibiotics, has bacteriostatic effect on multidrug-resistant bacteria such as carbapenem-resistant Acinetobacter and Klebsiella pneumoniae, and its binding ability to bacterial ribosomes is stronger than that of other tetracycline antibiotics, so it is often used clinically in the treatment of complex skin and soft tissue infections, intra-abdominal infections, acquired pneumonia, and other diseases in adults [ 10 ]. Many studies showed that tigecycline had positive in vitro antibacterial activity against resistant Acinetobacter baumannii, but sole use of it may lead to resistant bacteria [ 11 , 12 ]. Cefoperazone sulbactam sodium, the broad-spectrum antibiotic, has a certain therapeutic effect on respiratory tract infections, urogenital infections, intra-abdominal infections, bone and joint infections, intracranial infections, and skin and soft tissue infections caused by sensitive bacteria [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three case reports in patients receiving tigecycline 50 mg intravenous twice-daily with CNS infections show a penetration ratio of between 0.07 and 0.85 based on point estimate comparisons with CSF concentrations ranging from 0.035 to 0.048 mg/L [74][75][76]. Intraventricular tigecycline administration has been used in small case series and case reports using doses up to 4 mg daily, which does not appear to be based on PK/PD targets [77][78][79][80]. One case report describes an approximate CSF AUC 0-24 of approximately 67 after a 1 mg twice-daily intraventricular dose and a CSF AUC 0-12 of approximately 670 with a 5 mg twice-daily intraventricular dose [81].…”
Section: Tigecyclinementioning
confidence: 99%
“…Therefore, IVT administration is suggested in combination with IV carbapenems. 67 The guideline of the Infectious Diseases Society of America suggests that therapy should continue for 10 to 14 days after the last positive culture. 13 In 2018, the first pediatric IVT delivery of tigecycline was reported; the patient was an 8-month-old infant infected with XDR Klebsiella spp.…”
Section: Discussionmentioning
confidence: 99%